Impact of area-wide extension approach for bio-management of rhinoceros beetle with Metarhizium anisopliae - Chandrika Mohan, P. Anithakumari, K. Muralidharan (Journal of Plantation Crops, 2016)
Area-wide community extension approach (AWCA) was pilot tested for bio-management of rhinoceros beetle in Edava panchayat of Thiruvananthapuram district, Kerala state during the period 2010-2013. It focused on holdings having potential breeding sites of the pest and were treated with green muscardine fungus (GMF) Metarhizium anisopliae (Metsch.), multiplied at farm level by trained farm women groups. The project was implemented as participatory action research in an area of 520 ha of coconut involving over 5500 small and marginal farmers and stakeholders. AWCA proved to reduce the variability of technology impact in pest management compared to individual level of adoption. Significant reduction in the percentage incidence of rhinoceros beetles (72.9 ± 9.3 to 58.1 ± 9.3) was achieved in Edava panchayat whereas, it was more or less same (74.5%) during the period 2010-2013 in a non-intervention area (Kottamkara panchayat in Kollam district), where, only conventional extension approach followed. Similarly the average number of symptoms in coconut fronds per palm was also found to be reduced in AWCA area. It ranged from 1.6 to 4.6 before interventions and reduced to a range of 1.0 to 2.8 after interventions. In the non-intervention area it remained almost same (2.9 and 3.0 cuts per palm, respectively in 2010 and 2013). Impact of AWCA was observed to be more or less geographically contiguous on depicting the percentage reduction in severity of rhinoceros infestation in different wards of Edava panchayat using GIS tools.